Morphometrics of Heterotrigona Itama Nest Components in the Pocut Meurah Intan Grand Forest Park, Aceh Besar Regency, Indonesia - Dilla Sriwahyuni; Suwarno Suwarno; Alia Rizki; Zuriana Siregar (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to describe the morphometrics of the nest components of the stingless bee species of the Heterotrigona itama species in the Pocut Meurah Intan Grand Forest Park, Aceh Besar Regency, Indonesia. This research method uses direct observation of five H.itama nest colonies which includes measurements of each nest component, namely baby cells, pollen pots, honey pots and nest entrances. The results of this study reported that the nest components of five H.itama colonies had varying sizes. The entrance to the H. itama nest is tube-shaped with a tube length of 2.50 - 18.00 cm and a diameter of 1.50 - 4.50 cm. The diameters of pollen pots, honey pots and daughter cells are in the range of 0.95 - 1.14 cm, 0.65 - 1.14 cm and 0.30 - 0.34 cm respectively. The height of the pollen pot, honey pot and daughter cells ranges from 1.24 - 1.64 cm, 0.63 - 1.20 cm and 0.44 - 0.50 cm respectively. From the results of this research, it can be concluded that H.itama found in the Pocut Meurah Intan Grand Forest Park, Aceh Besar Regency, Indonesia has varying morphometrics in each colony.